Komodifikasi Identitas Cross Gender pada Content Creator dalam Memenuhi Tuntutan Algoritma Di Media Sosial - Ando Ramadika; Lisa Adhrianti; Neneng Cucu Marlina (STAI Bumi Silampari, 2026)
This research is motivated by the shift in cross-gender identities on social media, which are no longer simply self-expression but have become commodified within the system of digital platform capitalism, particularly among content creators in Bengkulu. This study aims to analyze these commodification practices through the creators' lived experiences constructing, negotiating, and monetizing their identities. The method used is qualitative with a phenomenological approach through in-depth interviews and observations of two local content creators. The results show that cross-gender identities have been integrated into the logic of the platform economy, where algorithms influence content visibility and strategy, while the attention economy drives production intensity and audience engagement. The identities displayed become economically valuable commodities in commercial partnerships, and creators' activities reflect flexible digital labor without clear work boundaries. Furthermore, there is a negotiation between local Bengkulu culture and the demands of global platform capitalism in the packaging of identities. Therefore, creators' digital identities are not neutral but are shaped by the power relations of technology and the platform economy.